Mājhā aṭakepāra pravāsa - Bhāṭe, Govinda Cimaṇājī, 1870-1946 (Bhāṭe, Govinda Cimaṇajī, 1870-1946. Pravāsavrttamālā ;, 1935)
Travel account of the author's visit to North-west Frontier Province, Pakistan.